Change by Design: How Design Thinking Transforms Organizations and Inspires Innovation - and Brown, Tim (HarperBusiness, 2009)
The myth of innovation is that brilliant ideas leap fully formed from the minds of geniuses. The reality is that most innovations come from a process of rigorous examination through which great ideas are identified and developed before being realized as new offerings and capabilities. This book introduces the idea of design thinking the collaborative process by which the designer's sensibilities and methods are employed to match people's needs not only with what is technically feasible and a viable business strategy. In short design thinking converts need into demand. It's a human-centered approach to problem solving that helps people and organizations become more innovative and more creative. Design thinking is not just applicable to so-called creative industries or people who work in the design field. It's a methodology that has been used by organizations such as Kaiser Permanente to increase the quality of patient care by re-examining the ways that their nurses manage shift change or Kraft to rethink supply chain management. This is not a book by designers for designers; this is a book for creative leaders seeking to infuse design thinking into every level of an organization product or service to drive new alternatives for business and society.
Keywords: IMPORTANT